Synthesis and Antimicrobial Activity of 1,2,4-Triazolo[4,3-b][1,2,4,5]tetrazines - M.A. Altalbawy, Farag; S.S. Darwish, Elham (Asian Journal of Chemistry, 2011)
Synthesis of 4-phenylamino-5-phenyl-4H-[1,2,4]triazole-3-thiol (1) and 3-methylthio-4- phenylamino-5-phenyl-4H-[1,2,4]triazole (2) is described. Reactions of hydrazonoyl halides (3) with either 1 or 2 afforded 1,2,4-triazol[4,3-b][1,2,4,5]tetrazine. The latter products were screened for their antifungal and antibacterial properties. The structure of the products was established based on elemental and spectral analyses. Further evidence for the assigned structure of the products is based on alternative synthesis. The mechanism of the studied reactions was also discussed.